The Economic Development of Somalia Telecommunication Sector in the Absence of An Effective Regulatory Body: Evidences from Mogadishu - Somalia - ABDULQADIR, ABUBAKAR SHEIKH HASSAN GELLE (2019)
The purpose of this research is to investigate the economic development of the Somalia private sector in the absence of an effective regulatory body or framework. Private sector firms in the telecommunication industry within Mogadishu City, Somalia, have been selected as the case for study. The study has been divided into four specific objectives. These objectives are: To examine the characteristics and conditions under which the private telecommunication firms in Somali currently operate; To analyse the strengths and weaknesses of the private telecommunication firms in Somalia today; To explore the main challenges faced by the Somali private sector presently; and To discuss the role the State can play to ensure a sustainable growth agenda of the private sector in Somalia now and in the future. In order to achieve the above-mentioned objectives, the study was divided into five chapters, and each chapter was divided into a number of sections and sub-sections. As far as the research methodology is concerned, this study employed a mixed research design by using both descriptive and case study research designs due to the nature of the data to be collected for analysis. The study also employed the use of probability and non-probability sampling techniques, where stratified random sampling and purposive sampling procedures were used. Data was collected through primary sources using structured questionnaires, interview guides, and observations. The data to be collected during fieldwork was subjected to both quantitative and qualitative analysis techniques, where quantitative data was analysed using the SPSS tool, while qualitative data was analysed using thematic grouping and content analysis. The analysed data were presented in the form of frequency tables, charts, and graphs. The study concludes that weaknesses and strengths had a significant effect on the economic development of the telecommunication sector in Somalia; the telecom sector in Somalia lacks adequate qualified personnel and a shortage of sufficient economic development stimulators or incubators. The telecom sector in Somalia suffers from increased competition in unregulated markets and the prevalent risk of balkanisation coupled with tribal breakup has negatively affected the development of the telecom sector. The study concludes that the telecom sector faces many challenges that limit this sector, including access to finance. The study concludes that the current regime has barely done little to foster a conducive environment upon which a vibrant telecommunication industry can be built, the government of Somalia lacks adequate capability to collect domestic tax and pay external debts and the government had a role in facilitating and support the development of efficient and secure nationwide communications infrastructure that provides affordable and pervasive broadband connectivity and accelerates socio-economic development in all parts of Somalia, this study recommends that the Somali government should limit the regulatory burden on the private sector with ‘light touch’ customer-centric regulation to promote innovation and encourage the free flow of information while ensuring the necessary checks and balances are in place that ensures the protection of the public, a level playing field and sustainability/reliability of services. The Somalian government should establish a strong legal environment and facilitate and support the development of efficient and secure nationwide communications infrastructure that provides affordable and pervasive broadband connectivity and accelerates socio-economic development in all parts of Somalia, where necessary.